Effect of lower extremity weightbearing load on motoneuron excitability in able-bodied subjects - Field-Fote, E C; Hufford, T; Kerfoot, N; Kizer, S; Calancie, B (Electromyography and clinical neurophysiology, 2000)
Body weight support (BWS) is becoming an increasingly tool popular in rehabilitation settings, but little is known about how weight support effects reflex activity. Lower extremity Hoffman (H) reflex and tendon reflex responses were used to assess motoneuron excitability as a function of static lower extremity weightbearing load in neurologically normal individuals. Factors that are known to affect reflex activity, such as body orientation, movement and task phase were kept constant. Twenty three subjects were studied under three static load conditions (50%, 75% and 100% weightbearing) using four different stimulus conditions (soleus H-reflex, soleus H-reflex with vibration, Achilles tendon reflex, quadriceps tendon reflex). Load had no effect on any of the reflexes studied; we hypothesize that under static conditions, lower extremity reflexes are not affected by superincumbent load.